Blended approaches to English as a foreign language instruction - Daly, Avian (My University, 2015)
The teaching of English as a Foreign Language (EFL) in the English-speaking Caribbean is becoming a lucrative branch of the tertiary education sector. While some learners seek a fully immersive experience, others prefer a blended option to accommodate personal and professional schedules. Regardless of the desired experience, the current regional trend suggests a significant shift from mainstream US/UK EFL providers toward the English-speaking Caribbean for accredited, cost-effective, alternative modes of instruction. This phenomenon presents unique challenges to the English-speaking Caribbean, as our institutions of higher education (HE) seek to establish themselves as leaders in the field of EFL instruction. This theoretical paper therefore critically assesses best practices in blended approaches as presented in the literature, namely, the use of the learning management system, Moodle, and video-conferencing technology, in response to the demand for online EFL instruction adapted to the Caribbean context. An analysis of the aforementioned practices will provide greater insight into the challenges that may be encountered in online EFL delivery for the EFL programme at the UWI St. Augustine.
Contribution to the Panel on New Directions in Foreign Language Research in Caribbean Higher Education at the Regional Conference on Institutionalising Best Practice in Higher Education, UWI, St. Augustine, Trinidad and Tobago, 24-26 June, 2015.
Keywords: Foreign language education; Higher education; English as a foreign language; Best practices; Blended learning; The University of the West Indies, St. Augustine